Chloroplast Translation Elongation Factor EF-Tu/SVR11 Is Involved in var2-Mediated Leaf Variegation and Leaf Development in Arabidopsis - Liu, Siyu; Zheng, Lu; Jia, Jia; Guo, Jia; Zheng, Mengdi; Zhao, Jun; Shao, Jingxia; Liu, Xiayan; An, Lijun; Yu, Fei; Qi, Yafei (Frontiers in Plant Science, 2019)
Chloroplasts are semiautonomous organelles, retaining their own genomes and gene expression apparatuses but controlled by nucleus genome encoded protein factors during evolution. To analyze the genetic regulatory network of FtsH-mediated chloroplast development in Arabidopsis, a set of suppressor mutants of yellow variegated (var2) have been identified. In this research, we reported the identification of another new var2 suppressor locus, SUPPRESSOR OF VARIEGATION11 (SVR11), which encodes a putative chloroplast-localized prokaryotic type translation elongation factor EF-Tu. SVR11 is likely essential to chloroplast development and plant survival. GUS activity reveals that SVR11 is abundant in the juvenile leaf tissue, lateral roots and root tips. Interestingly, we found that SVR11 and SVR9 together regulate leaf development, including leaf margin development and cotyledon venation patterns. These findings reinforce the notion that chloroplast translation state triggers retrograde signals regulate not only chloroplast development but also leaf development.